Effect of scavenger receptor class B type I antagonist ITX5061 in patients with hepatitis C virus infection undergoing liver transplantation. Issue 3 (March 2016) - Rowe, Ian A.; Tully, Damien C.; Armstrong, Matthew J.; Parker, Richard; Guo, Kathy; Barton, Darren; Morse, Gene D.; Venuto, Charles S.; Ogilvie, Colin B.; Hedegaard, Ditte L.; McKelvy, Jeffrey F.; Wong‐Staal, Flossie; et al.
Abstract : Hepatitis C virus (HCV) entry inhibitors have been hypothesized to prevent infection of the liver after transplantation. ITX5061 is a scavenger receptor class B type I antagonist that blocks HCV entry and infection in vitro. We assessed the safety and efficacy of ITX5061 to limit HCV infection of the graft. The study included 23 HCV‐infected patients undergoing liver transplantation. The first 13 "control" patients did not receive drug. The subsequent 10 patients received 150 mg of ITX5061 immediately before and after transplant and daily for 1 week thereafter. ITX5061 pharmacokinetics and plasma HCV RNA were quantified. Viral genetic diversity was measured by ultradeep pyrosequencing (UDPS). ITX5061 was well tolerated with measurable plasma concentrations during therapy. Although the median HCV RNA reduction was greater in ITX‐treated patients at all time points in the first week after transplantation, there was no difference in the overall change in the area over the HCV RNA curve in the 7‐day treatment period. However, in genotype (GT) 1–infected patients, treatment was associated with a sustained reduction in HCV RNA levels compared to the control group (area over the HCV RNA curve analysis, P = 0.004). UDPS revealed a complex and evolving pattern of HCV variants infecting the graft during the first week. ITX5061 significantly limited viral evolution where the median divergence between day 0 and day 7 was 3.5% in the control group compared to 0.1% in the treated group. In conclusion, ITX5061 reduces plasma HCV RNA after transplant notably in GT 1–infected patients and slows viral evolution. Following liver transplantation, the likely contribution of extrahepatic reservoirs of HCV necessitates combining entry inhibitors such as ITX5061 with inhibitors of replication in future studies. Liver Transpl 22:287‐297, 2016 . © 2015 AASLD.